Comparative Study Of Functional Properties And Nutritive Value Of Manilkara Zapota (Sapodilla) Flesh And Peel Powder At Different Maturity - Abdul Rashid, Siti Nur Antasha (Enhanced Knowledge in Sciences and Technology, 2022)
Sapodilla (Manilkara Zapota) belongs to the family Sapotaceae was known for various properties which can bring to health benefit. However, limited shelf life of fruit and waste of sapodilla peels can lead to food waste and loss of nutrients and excellent biomass. A study has been made to investigate the effect of maturity from flesh and peel by transform the raw fruit into powder to increase the shelf life. Physicochemical analysis was held to investigate the pH value, total soluble solid (TSS), titratable acidity (TA), ascorbic acid content, antioxidant capacity and total phenolic content. From the studies, pH value was high in sapodilla peel at day 3 (4.97c± 0.01) than sapodilla flesh (5.05c± 0.01) and other storage time. TSS value of mature ripe sapodilla flesh (6.10a ± 0.00) higher than sapodilla peel. Higher citric acid content was identified in sapodilla flesh in day 3 (0.20a ± 0.15) and declines as increasing maturity stage for day 4 and 8. For ascorbic acid content, sapodilla peel poses higher value which is 12.12a ± 0.06 mg/100g than sapodilla flesh 9.85ab ± 0.06 mg/100g. Antioxidant content of sapodilla peel at day 3 was observed have higher inhibition than sapodilla flesh while phenolic content of the sapodilla peel yields higher TPC at day 3 (0.0855a ± 0.0113 mg GAE/g) than other storage time and sapodilla flesh at day 3 (0.0745ab ± 0.0028 mg GAE/g). Spectral analysis proven the presence of the phenolic content which present in the O-H stretch and C-O stretch in sapodilla peel at day 4 and sapodilla flesh at day 3. From the studies, it shows that sapodilla peel consists of higher antioxidant content than sapodilla flesh.